ATTRIBUTE FACTORS INFLUENCING CUSTOMER OVERALL SATISFACTION IN HOTEL SERVICES – EXAMPLE OF GEORGIA - Nana Katsitadze; Natalia Kharadze; Maia Giorgobiani (Baltic Journal of Economic Studies, 2025)
The present research focuses on measuring service quality and customer satisfaction in the hotel industry. The aim is to identify overall satisfaction with hotel services in Georgia and the factors influencing it. This issue is of particular pertinence, given its impact on both the image of the country as a tourist destination and the prospects for guests returning from their travels with a sense of satisfaction. This is of particular significance for Georgia, which is currently engaged in efforts to consolidate its position within the global tourism market. The study utilised statistical data from official organisations, as well as ratings reflecting the overall satisfaction of guests surveyed using modern technology on the Booking.com portal. Qualitative factors were grouped into 6-7 sub-components impacting satisfaction, which were formulated by sharing the concept of popular models. The research has utilised the results of a survey of confirmed guests in 137 hotels located in the city of Tbilisi and mountain resorts (8,874 respondents). The results were processed using the SPSS statistical software package. A comparative analysis of hotel cluster groups was conducted, which revealed that local hotel brands have competitive strategies, such as their uniqueness, and different customer attitudes towards quality components of different categories of hotels. This was reflected in the high satisfaction with family hotels in this segment, despite their low ratings in certain (predominantly technical) components of quality. It is noteworthy that interest in mountain resort brands is growing; therefore, family hotels, which make a significant contribution to the sustainable development of regional tourism, require support from the state through different approaches, such as raising knowledge of the area and regulatory incentives. It is evident that the limitations imposed by the research have precluded an assessment of the weighted significance of the impact of the indicators – quality factor groups – on the hotel's rating. This is a subject that requires further study.